All Days 2006
DOI: 10.2118/100233-ms
|View full text |Cite
|
Sign up to set email alerts
|

From Logs Scale to Reservoir Scale: Upscaling of the Petroelastic Model

Abstract: Any quantitative workflow, designed to constrain reservoir models to 3D/4D seismic data, must rely on petro-elastic modelling (or PEM), which relates fluid and rock properties to elastic ones. Various scales must be accounted for: laboratory cores and well logs, geological and seismic grids, fluid flow simulator models. The petro-elastic model is generally a fine-scale model ("pem"), defined and calibrated for each specific case against core and logs data. Aiming a 4D histor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Secondly, there is uncertainty in the equations used to calculate the synthetic seismic data because they were derived from lab studies and they may be unsuitable for the simulation scale or for in situ calculations (Menezes and Gosselin 2006;Kazemi and Modin 2010). We found that the choice of model did not matter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, there is uncertainty in the equations used to calculate the synthetic seismic data because they were derived from lab studies and they may be unsuitable for the simulation scale or for in situ calculations (Menezes and Gosselin 2006;Kazemi and Modin 2010). We found that the choice of model did not matter.…”
Section: Discussionmentioning
confidence: 99%
“…Uncertainties may arise in the prediction however, because of averaging issues when transforming from well logs to simulation cells. Secondly, there is uncertainty in the equations used to calculate the synthetic seismic data because they were derived from lab studies and they may be unsuitable for the simulation scale or for in situ calculations (Menezes and Gosselin 2006;Kazemi and Modin 2010).…”
Section: Discussionmentioning
confidence: 99%